Numerical Simulations for Analysis of Face Stability of Tunnelling (Journal of Building and Road Research, 2021)
The aim of this paper is to evaluate numerical procedures that are used for analysis of face stability of a tunnelling. Two-dimensional (2D) and threedimensional (3D) Finite Element (FE) modelling of the Second Heinenoord Tunnel in Netherlands were done by using PLAXIS programs. The models were simulated the tunnel boring machine (TBM) with shell element and the slurry pressure with applied face pressure that measured in the site from the literature. Two methods were used to determine the situation of face failure. The first method was done by reducing the applied face pressure until the failure of the face was occurred, so the minimum required face pressure was determined. The second one was done by reducing the shear strength of the soil until the face failure, so the safety factor was determined. Both methods were applied for 2D and 3D FE-modelling. The results were presented and discussed. Also, the results of the minimum required support pressure were compared to the result of the centrifugal test model for the Second Heinenoord Tunnel found in literature. It was found that, the reducing applied face pressure method is much better than the reducing shear strength method. Also, the result of 3D FE-modelling gave better prediction when comparing with the experimental result .
Keywords: Tunnels; numerical modelling; heading stability; safety factor; face pressure